2018
DOI: 10.1007/s00348-018-2566-4
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of miscible viscous fingering by a step growth polymerization reaction

Abstract: Fingering is a hydrodynamic instability that occurs when a more mobile fluid displaces a fluid of lower mobility. When the primary source of the mobility difference is viscosity, the instability is termed viscous fingering. Viscous fingering is often, though not always, undesirable in industrial processes, particularly secondary petroleum recovery. Linear stability analysis by Hejazi et al. has indicated that the production of a non-monotonic viscosity profile can stabilize the interface. Herein, we use step-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The case of reactions inducing a non-monotonic increasing viscosity profile with a maximum (zone III of Figure 3) has been recently studied in Hele-Shaw cells in the case of a step-growth cross-linking polymerization reaction (Bunton et al (2017), Stewart et al (2018)). In absence of reaction, the invading solution is less viscous than the displaced one and VF is obtained.…”
Section: Viscous Fingering Ofmentioning
confidence: 99%
“…The case of reactions inducing a non-monotonic increasing viscosity profile with a maximum (zone III of Figure 3) has been recently studied in Hele-Shaw cells in the case of a step-growth cross-linking polymerization reaction (Bunton et al (2017), Stewart et al (2018)). In absence of reaction, the invading solution is less viscous than the displaced one and VF is obtained.…”
Section: Viscous Fingering Ofmentioning
confidence: 99%
“…In reality, the various chemical species involved typically do not diffuse at the same rate as when the reaction produces or consumes big molecules like polymers or micelles, for instance [19,32,33]. Differential diffusion effects might then play an important role in fingering as shown previously [21,44,45].…”
Section: B Nondimensional Equationsmentioning
confidence: 99%
“…The bistable nature of chemical kinetics is then responsible for a new phenomenon of droplet formation isolating regions of high or low viscosity within connected domains of the other steady state. In other studies, the active influence of A + B → C types of chemical reactions on miscible VF has been studied both experimentally [19,20,22,[27][28][29][31][32][33] and theoretically [21,[23][24][25][26]28,30,34]. Various fingering regimes have been identified depending on concentrations, fluid characteristics, and injection flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Research in pH-sensitive materials is a major subject in science due to possible applications in a broad variety of fields. Just to name a few, many innovative medical therapies are focused on the use of pH-responsive systems to test drug-targeting techniques. , Recently, several experimental studies have reported the possibility to control and modulate the hydrodynamic viscous fingering instability by using chemical neutralization reactions coupled with pH-sensitive polymers or polymerization reactions. , Viscous fingering typically occurs when a low-viscosity solution displaces a more viscous one and leads to increased mixing between the two liquids. It can be detrimental in chemical and petroleum , applications, which explains the experimental and theoretical , efforts devoted to control this hydrodynamic instability by in situ chemically driven viscosity changes. , …”
Section: Introductionmentioning
confidence: 99%